Economic and political autonomy of women in latin america : a multidimensional analysis of evolution and inequalities (2024)
In recent years, there has been a growing international interest in understanding gender inequality in various social spheres, in this sense; organizations have been dedicated to promoting the economic development of countries seeking alternatives to strengthen equality, promoting political agreements and actions. The objective was to analyze the economic and political autonomy of Latin American women. The quantitative methodology with exploratory scope, using the Statis multivariate statistical technique, the multidimensional interaction between 10 indicators of economic and political autonomy of Latin American women, according to figures compiled by the Gender Observatory of the United Nations Economic Commission for Latin America and the Caribbean. Results, gender indicators were analyzed in 16 Latin American countries between 2005 and 2019, where improvements were observed in the political participation of women in certain countries and an increase in women in high productivity sectors, economic and political autonomy showed an independent relationship, these results are relevant to address gender equity in the region. Concluding that there are considerable differences between nations, which imply a heterogeneous evolution in the search for gender parity in the political and economic spheres of the region.